Participation in school sport in the Region of Murcia: public versus semi-private and private centers - Morales, V.; Martínez-Moreno, A.; Díaz, A. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2016)
It is considered as a source the data from the General Directorate of the Physical Activity and Sports (Dirección General de Actividad Física y Deportes) in the Region of Murcia. In this study, it is delimited the number of participants, ratio of participation and the average of the participation in relation to the population, that is, how many participations per person are taken place relating to Sport in school-age in the Region of Murcia during the period of the academic years from 2005 to 2010. The sample is formed by 155.009 masculine participants and 94.317 feminine participants from public and state-subsidized private schools. The participation in state-subsidized private schools was 24,83% (193.628 registered) versus the 36,72% (548.100 registered) in public schools. The participation in relation to the ratio per person was also biased in favor of the public schools (0,457 facing the 0,268 of the state-subsidized private schools). Therefore, data showed that the number of participations in relative and absolute terms is greater in public schools.